Theoretical Analysis of Ionizing Radiation Shielding Properties of Tungsten Based Alloy Used in Fusion Nuclear Reactor - Sriwongsa, Kittisak; Glumglomchit, Punsak; Tiensomboon, Phupa; Liamnark, Suppawit; Kamkhlay, Thanachot; Ravangvong, Sunantasak (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
The aim of this research was to study the radiation, fast neutron and charge particles of ionizing radiation (protons and alpha particles) shielding properties of tungsten-based alloys for 6 samples, namely MT-17C, MT-17F, MT-175, MT-18C, MT-18F, and MT-185. The radiation shielding properties were discussed based on mass attenuation coefficient (μm), effective atomic number (Zeff), half value layer (HVL) and mean free path (MFP) values. These values were calculated using Phy-X/PSD program at energy ranging between 10-3 - 105 MeV. Fast neutron shielding properties were explained by fast neutron removal cross sections ( ) which were determined using partial density. For charge, particles of ionizing radiation (protons and alpha particles) were simulated using SRIM program, version 2013, at energy ranging between 0.1 - 15 MeV. The parameters analyzed were mass stopping power (MSP) and project ranged (PR). The results revealed that MT-185 tungsten-based alloy had an excellent radiation, fast neutron and charge particles of ionizing radiation (protons and alpha particles) shielding properties.